Volatile, Microbial, and Sensory Profiles and Consumer Acceptance of Coffee Cascara Kombuchas - Amanda Luísa Sales; Sara C. Cunha; Jéssika Morgado; Adriano Cruz; Thiago F. Santos; Isabel M.P.L.V.O. Ferreira; José O. Fernandes; Marco Antonio L. Miguel; Adriana Farah (Foods, 2023)
Given the substantial world coffee production, tons of coffee fruit cascara rich in bioactive compounds are discarded annually. Using this by-product to produce potentially healthy and acceptable foods is a sustainable practice that aggregates value to coffee production and may help improve people’s lives. This study aimed to elaborate kombuchas from coffee cascara tea, evaluate their microbial profile, and monitor the changes in the volatile profile during fermentation, together with sensory attributes and acceptance by consumers from Rio de Janeiro (n = 113). Arabica coffee cascaras from Brazil and Nicaragua were used to make infusions, to which black tea kombucha, a Symbiotic Culture of Bacteria and Yeasts (SCOBY), and sucrose were added. Fermentation of plain black tea kombucha was also monitored for comparison. The volatile profile was analyzed after 0, 3, 6, and 9 days of fermentation via headspace solid phase microextraction GC-MS. A total of 81 compounds were identified considering all beverages, 59 in coffee cascara kombuchas and 59 in the black tea kombucha, with 37 common compounds for both. An increase mainly in acids and esters occurred during fermentation. Despite the similarity to black tea kombucha, some aldehydes, esters, alcohols, and ketones in coffee cascara kombucha were not identified in black tea kombucha. Potential impact compounds in CC were linalool, decanal, nonanal, octanal, dodecanal, ethanol, 2-ethylhexanol, ethyl acetate, ethyl butyrate, ethyl acetate, β-damascenone, γ-nonalactone, linalool oxide, phenylethyl alcohol, geranyl acetone, phenylacetaldehyde, isoamyl alcohol, acetic acid, octanoic acid, isovaleric acid, ethyl isobutyrate, ethyl hexanoate, and limonene. The mean acceptance scores for cascara kombuchas varied between 5.7 ± 0.53 and 7.4 ± 0.53 on a nine-point hedonic scale, with coffee cascara from three-day Nicaragua kombucha showing the highest score, associated with sweetness and berry, honey, woody, and herbal aromas and flavors. The present results indicate that coffee cascara is a promising by-product for elaboration of fermented beverages, exhibiting exotic and singular fingerprinting that can be explored for applications in the food industry.